Penyaluran Zakat Produktif Melalui Program Taman Pendidikan Al-Quran Di Kampung Zakat Terpadu Kabupaten Jember - Mahfiyah Mahfiyah; Andri Cahyono Sofyan; Achmad Fawaid (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
This research aims to examine the concept of productive zakat distribution through the TPQ Darul Quran program and its impact on the community in the Integrated Zakat Village. The Integrated Zakat Village is the first Zakat Village in East Java which is located in a remote area in Jember Regency and the majority of residents in the Zakat Village area are underprivileged people. This research uses a qualitative approach. Data collection methods use interviews, observation and documentation. Determining informants using purposive techniques and data analysis in this research includes data reduction, data presentation, data condensation and drawing conclusions. The results of this research show: 1) there are two types of concept for distributing zakat through TPQ Darul Quran in the Integrated Zakat Village, namely creative productive distribution and creative consumptive distribution. 2) The existence of the TPQ Darul Quran program is very beneficial for the people of Paceh Hamlet because many children can learn to recite the Quran as well as study religious knowledge for free. In fact, with the large number of children studying at TPQ, it is starting to stimulate the economy of the surrounding community because several people can sell around the TPQ.